Faith in the Research Process: Information Behavior at Claremont School of Theology - Milas, T. Patrick (Journal of religious and theological information, 2020)
Faith significantly affects the educational experience in graduate studies of religion and theology. This study explored the roles of graduate theological students' religious faith and degree program affiliation in their information behaviors, particularly their degree-related research behaviors at Claremont School of Theology. The purpose was to explore problems in information action inherent to the dichotomy between academic study of theology that leads to Master of Arts (MA) degree and professional study of theology that leads to Master of Divinity (MDiv) degree. The research design incorporated interviews of MA and MDiv students regarding the roles of their religious faith, degree program affiliation and interpersonal information sources in their research processes. Data were collected, coded and analyzed as a lens into the social network of the theological research community. The study found that information behavior does relate to degree program affiliations and students' religious faith. Degree program affiliation and religious faith background are relevant to graduate theological research processes and may be useful to consider in research consultations and bibliographic instruction in graduate theological education.